Impact of Disease Disclosure on Stigma: An Experimental Investigation of College Students' Reactions to Inflammatory Bowel Disease. Issue 1 (2nd January 2018) - Rohde, Jacob A.; Wang, Yue; Cutino, Chelsea M.; Dickson, Bonnie K.; Bernal, Marisa C.; Bronda, Serena; Liu, Aizhou; Priyadarshini, Sai Indira; Guo, Ling; Reich, Jason S.; Farraye, Francis A.
Abstract : Inflammatory bowel disease (IBD) is a serious chronic illness that affects 1 in 200 people in the United States with the majority of new cases of IBD diagnosed in young people under the age of 35. Despite the growing number of people who are diagnosed each year, the consequences of health-related stigma faced by young people grappling with the effects of IBD are understudied. This experimental investigation explored the existence of enacted stigma among college students, a population that faces many social and psychological challenges due to the added emotional stresses brought about by the transition from high school and adolescence to college and adulthood. Results indicate that enacted stigma among college students toward other students with IBD decreases when disclosure of the disease is present. Results also suggest that greater knowledge of the nature and symptoms of IBD positively correlates to decreased stigma.